Captive breeding, developmental biology and commercial production of Dravidia fasciata- An indigenous ornamental fish of the Western Ghats of India - T.V. Anna Mercy; Eapen Jacob; K. Raju Thomas (East African Journal of Biophysical and Computational Sciences)
Ornamental fishes of the Western Ghats of India have great demand in the export market. At present these fishes are collected from the wild and exported. Hence many times, the demand could not be met due to short supply. The only remedial measure for a sustainable supply is to produce the fish in captive conditions. Unfortunately, the breeding technology for the ornamental fishes of the Western Ghats of India has not been attempted seriously till date. The present paper is almost a pioneering attempt to develop captive breeding technology for 12 prioritized species of the indigenous ornamental fishes of the Western Ghats of India. Dravidia fasciata is one of them. It is popularly known as Melon barb. It is a beautiful barb, growing to a maximum size of 80 mm. In the present paper the methodology of captive breeding of this fish is provided with the economics of its production. Melon barbs were collected from the wild and brought to the hatchery of College of Fisheries in oxygen filled plastic bags and gradually acclimatized to the captive conditions. Its size at first maturity, sexual dimorphism, and developmental biology were studied and described with photographs. The total length (TL) at first maturity for males was 50 mm (50-55 mm) and 40 mm for females (40-45 mm). A sexually mature male developed beautiful pinkish red tinge all over the body. The black bands over the body also became deeper in colour during this time. The intensity of the colour reached its maximum during the courtship activities. Male also possessed nuptial tubercles on the operculum which could be identified only by keen observation. But a sexually mature female did not develop any colour change by the onset of sexual maturity. The results of the study clearly demonstrated that D. fasciata could be successfully produced in captivity through scientific management of brooders, eggs, larvae and hatchlings. The successful development of captive breeding technology is likely to pave way towards commercialization of the technology thus leading to the sustainable export of the species.